Current issues of quality of life in peripheral municipalities of large urban agglomerations (using the Moscow region as an example) - N.A. Ponomarev (Векторы благополучия: экономика и социум)
The research is devoted to the study of the issue of the most significant elements of the quality of life in the territory of peripheral municipalities of large urban agglomerations. Municipalities of the Moscow region, forming the periphery of the capital agglomeration, are singled out as research cases. The relevance of the study is due to the need to clarify the issue of the structure of the problems of socio‐economic development of settlements located on the periphery of large agglomerations, relative to the period of the 2000s – 2010s. The methodology of the work is built by combining an expert survey with elements of comparative and structural analysis. It is concluded that the core of the current problems of the quality of life of peripheral municipalities of large agglomerations is formed by the shortage of social infrastructure facilities, a high degree of depreciation of fixed assets of housing and communal services, a shortage of narrow medical specialists and low availability of certain medical services, as well as a relatively low number of fairly well‐paid jobs, giving rise to mass pendulum migration. These problems were noted back in the 2000s. This indirectly indicates the limited effectiveness of previously adopted measures aimed at eliminating the listed problems and, possibly, changing the model of distribution between different levels of the public authority system of both powers and budgetary resources.